Alterations of color vision and pupillary light responses in age-related macular degeneration - Decleva, Diego; Vidal, Kallene Summer; Kreuz, Andre Carvalho; de Menezes, Paulo Augusto Hidalgo Leite; Ventura, Dora Fix (Frontiers in Aging Neuroscience, 2023)
Introduction Age-related macular degeneration (AMD) is the leading cause of irreversible central vision loss in developed countries and one of the leading causes of blindness. In this work, we evaluated color vision and the pupil light reflex (PLR) to assess visual function in patients with early and neovascular AMD (NVAMD) compared with the control group. Methods We recruited 34 early patients with dry AMD and classified them into two groups following AREDS: 13 patients with NVAMD and 24 healthy controls. Controls and patients with early dry AMD had visual acuity (VA) best or equal to 20/25 (0.098 logMAR). Color vision was assessed in controls and patients with early dry AMD using the Cambridge Color Test (CCT) 2.0 through the Trivector protocol. The PLR was evaluated using a Ganzfeld, controlled by the RETI–port system. The stimuli consisted of 1s blue (470 nm) and red (631 nm) light flashes presented alternately at 2-min intervals. To assess the cone contribution, we used a red flash at 2.4 log cd.m–2, with a blue background at 0.78 log cd.m–2. For rods, we used 470-nm flashes at –3 log cd.m–2, and for the melanopsin function of ipRGCs, we used 470 nm at 2.4 log cd.m–2. Results Patients with early dry AMD had reduced color discrimination in all three axes: protan (p = 0.0087), deutan (p = 0.0180), and tritan (p = 0.0095) when compared with the control group. The PLR has also been affected in patients with early dry AMD and patients with NVAMD. The amplitude for the melanopsin-driven response was smaller in patients with early dry AMD (p = 0.0485) and NVAMD (p = 0.0035) than in the control group. The melanopsin function was lower in patients with NVAMD (p = 0.0290) than the control group. For the rod-driven response, the latency was lower in the NVAMD group (p = 0.0041) than in the control group. No changes were found in cone-driven responses between the control and AMD groups. Conclusion Patients with early dry AMD present diffusely acquired color vision alteration detected by CCT. Rods and melanopsin contributions for PLR are affected in NVAMD. The CCT and the PLR may be considered sensitive tests to evaluate and monitor functional changes in patients with AMD.